Anthropometric Measures and Body Composition of Soccer Players of Montenegro and Kosovo - Dusko Bjelica; Jovan Gardasevic; Ivan Vasiljevic; Fitim Arifi; Sami Sermaxhaj (Journal of Anthropology of Sport and Physical Education, 2019)
The aim of this research was to determine the diff erences among the top soccer players of the Montenegrin club FC Mladost and Kosovian club FC Prishtina, in the anthropometric measures and body composition. A sample of 37 examinees is divided into two sub-samples. The fi rst sub-sample of the examinees consisted of 17 players of FC Mladost of the average age of 24.59±4.66, the vice champions of the Montenegrin Championship in the season 2016/17, while the other sub-sample consisted of 20 players of FC Prishtina of the average age of 24.30±4.99, the vice champions of the Kosovo Championship in the season 2016/17. Soccer players were tested immediately after the end of the competition season 2016/17. Anthropometric measures in the body composition were evaluated by a battery of 10 variables: body height, body weight, waist size, triceps skin set, biceps skin set, back skin set, abdominal skin set, body mass index, fat percentage and muscle mass. The standard central and dispersive parameters of all variables are calculated. The signifi cance of the diff erences between the players of the top two soccer clubs in the anthropometric measures and variables for assessing body composition was determined by a t-test for independent samples. It was found that the soccer players of the two mentioned clubs have statistically signifi cant diff erences by the two variables that estimate the body height in a favor of FC Mladost and abdominal skin set in a favor of FC Pristina.